A review of the Australian endemic clam shrimp, Paralimnadia Sars 1896 (Crustacea: Branchiopoda: Spinicaudata) - Timms, Brian V. (Zootaxa, 2016)
Paralimnadia was recently re-erected to accommodate Australian limnadiids formally placed in Limnadia. They are characterised by the lack of a spine on the posterior ventral corner of the telson, a cercopod divided by a spine midlength into a cylindrical seta bearing basal section and a narrowing denticle bearing distal section, males amplex females on the posterior body margin keeping the body in line, and gonochoristic reproduction, so typically sex ratios are broadly 1:1. These characters separate Paralimnadia from the closely related Eulimandia. Paralimnadia is endemic to and diverse in Australia, and includes the transferred P. stanleyana (King), P. sordida (King), P. badia (Wolf), P. cygnorum (Dakin) and P. urukhai (Webb & Bell) as well as 10 new species. All are variable morphologically, the most conservative characters being the morphology of their eggs and the cercopod setae. Although found across Australia, there are hot spots of diversity in the coast and montane areas of New South Wales and southwest of areas of Western Australia and few in the vast inland arid zone. As in Eulimnadia, a few occur in rock pools. However those in sandy coastal pools subject to urbanisation or mining are becoming rare.